2013
DOI: 10.14257/ijel.2013.2.2.05
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of E-Learning on some Psychological Dimensions and Academic Achievement

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 7 publications
0
12
0
1
Order By: Relevance
“…This finding corroborates the results of earlier studies (Alkhalaf et al, 2012;Bauk, 2015;Harandi, 2015) which all indicated that eLearning has a significant relationship to students" test anxiety. The results of Yazdi and Zandkarimi (2013) showed that e-learning in present site with teachers Teleworking and parent's virtual presence were more effective than the control group.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This finding corroborates the results of earlier studies (Alkhalaf et al, 2012;Bauk, 2015;Harandi, 2015) which all indicated that eLearning has a significant relationship to students" test anxiety. The results of Yazdi and Zandkarimi (2013) showed that e-learning in present site with teachers Teleworking and parent's virtual presence were more effective than the control group.…”
Section: Discussionmentioning
confidence: 86%
“…However, studies on e-learning show that it has a significant relationship with students' test anxiety (Alkhalaf et al, 2012;Bauk, 2015;Harandi, 2015). Yazdi and Zandkarimi (2013) measured students' achievement motivation and test anxiety at the beginning and end of their educational term which was assigned for pre-test and post-test scores. The results represented that elearning in present site with teachers Teleworking and parent's virtual presence were more effective than the control group.…”
Section: Introductionmentioning
confidence: 99%
“…We can conclude that these skills and abilities are developmental and are developed through experience, so teachers should certainly adjust their expectations and be more flexible during online classes. It is extremely important to keep in mind that students are in a developmental phase in which it is necessary to encourage the development of these skills and accordingly adjust some educational requirements of online teaching (Monavar Yazdi & Zandkarimi, 2013).…”
Section: Distance Learningmentioning
confidence: 99%
“…Penggunaan multimedia berupa video dalam pembelajaran blended learning yang disusun sendiri oleh dosen maupun di download dari youtube juga akan mempengaruhi pemahaman mahasiswa terhadap materi yang disampaikan. Menurut Yazdi & Zandkarimi (2013), pembelajaran dengan menggunakan media audio visual seperti video dapat memotivasi dan meningkatkan hasil pembelajaran. Hasil penelitian oleh Barak, Ashkar & Dori (2011) juga mengungkapkan bahwa penggunaan multimedia dapat meningkatkan motivasi belajar yang berkorelasi positif dengan kemampuan berpikir.…”
Section: Pembahasanunclassified